Pemodelan Pengetahuan Produk Body Moisturizer Menggunakan Pendekatan Ontologi Semantik - Sherly Martha Revania,; I Made Widhi Wirawan, (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
Indonesia's tropical climate poses significant challenges to skin health, particularly regarding body moisturizer selection. The abundance of products with varying ingredients and benefits often confuses consumers in choosing suitable products for their specific skin needs. This research develops a semantic ontology model for body moisturizer domain using the Methontology approach to provide structured and interconnected knowledge representation. The ontology was implemented using Protégé 5.6.5 and validated through Hermit Reasoner for consistency verification and SPARQL queries for functional testing. The developed ontology consists of 1 main class with 8 subclasses, 159 individuals, 3 data properties, and 14 object properties, covering essential aspects such as skin types, benefits, active ingredients, textures, and usage contexts. Evaluation results demonstrate that the ontology successfully responds to competency questions with accurate and contextually relevant results. The semantic model enables systematic organization of body moisturizer information, facilitating better product selection based on individual skin characteristics and environmental conditions in Indonesia's tropical climate.
Keywords: Ontology; Body Moisturizer; Methontology; Semantic Web; Skincare; Knowledge Representation